Early Childhood Studies: An introduction to the study of children`s lives and children worlds - Rod Parker-Rees & Caroline Leeson; Mandy Andrews; Dr Verity Campbell-Barr; Victoria Bamsey (London: SAGE, 2015)
This comprehensive, up-to-date core text covers all aspects of the early childhood studies course. Throughout, key theories and research findings are highlighted and explored to help readers make links between theory and early years practice.
Include Index
Adult
English